NOD2 polymorphisms in clinical phenotypes of common variable immunodeficiency disorders - Packwood, K (Blackwell Science Inc, 2010)
Common variable immunodeficiency disorders (CVIDs) are a heterogeneous group of diseases characterized by hypogammaglobulinaemia and consequent susceptibility to infection. CVID patients commonly develop a variety of additional manifestations for which the causative factors are not fully understood. Two such manifestations are granulomatous disease and enteropathy. Because the ability to predict complications would aid clinical management, we continue to search for possible disease modifier genes. NOD2 acts a microbial sensor and is involved in proinflammatory signalling. Particular mutations of the NOD2 gene are associated with Crohn's disease including gly908arg, leu1007finsc and arg702trp polymorphisms. We hypothesized that NOD2 polymorphisms may be a disease modifier gene towards an enteropathic or granulomatous phenotype within CVIDs. Sequence-specific primers returned genotypes for 285 CVID patients from centres across the United Kingdom and Europe. We present the frequencies of the different phenotypes of patients within our international cohort. Arg702trp polymorphisms were significantly less frequent than wild-type (WT) (P = 0·038) among international CVID patients with splenomegaly. Gly908arg polymorphisms were more prevalent than WT in UK patients with autoimmune disorders (P = 0·049) or enteropathy (P = 0·049). NOD2 polymorphisms were not more prevalent than WT in CVID patients with clinical phenotypes of granulomata. UK allele frequencies of 0·014, 0·056 and 0·026 were found for gly908arg, arg702trp and leu1007finsc NOD2 polymorphisms, respectively. These do not differ significantly from UK immunocompetent controls confirming, as expected, that in addition these NOD2 polymorphisms do not confer susceptibility to CVIDs per se.